2016
DOI: 10.3389/fbuil.2016.00033
|View full text |Cite
|
Sign up to set email alerts
|

Tsunami Hazard Analysis of Future Megathrust Sumatra Earthquakes in Padang, Indonesia Using Stochastic Tsunami Simulation

Abstract: This study assesses the tsunami hazard potential in Padang, Indonesia probabilistically using a novel stochastic tsunami simulation method. The stochastic tsunami simulation is conducted by generating multiple earthquake source models for a given earthquake scenario, which are used as input to run Monte Carlo tsunami simulation. Multiple earthquake source models for three magnitude scenarios, i.e., Mw 8.5, Mw 8.75, and Mw 9.0, are generated using new scaling relationships of earthquake source parameters develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Muhammad et al (2016) concluded that the regional earthquake source parameters calculated from the 19 past Sunda earthquakes are in good agreement with these scaling relationships; subsequently, the global models are adopted in this study. A set of 100 source models is then generated for each magnitude.…”
Section: Stochastic Tsunami Simulationmentioning
confidence: 83%
See 4 more Smart Citations
“…Muhammad et al (2016) concluded that the regional earthquake source parameters calculated from the 19 past Sunda earthquakes are in good agreement with these scaling relationships; subsequently, the global models are adopted in this study. A set of 100 source models is then generated for each magnitude.…”
Section: Stochastic Tsunami Simulationmentioning
confidence: 83%
“…In addition, in terms of selected magnitude scenarios, three scenario magnitudes are considered: M w 8.5, M w 8.75, and M w 9.0. The magnitude M w 8.5 is used as the minimum scenario because the tsunami hazard produced from the magnitude below this level, e.g., M w 8.25 and M w 8.0, is relatively small (less than 1 m wave height in the coastal areas; see Muhammad et al, 2016). The maximum magnitude scenario (M w 9.0) is selected based on paleogeodetic, geodetic, and paleotsunami studies (Zachariasen et al, 1999;Natawidjaja et al, 2006;Sieh et al, 2008); they indicated that the accumulated slip in the Mentawai segment of the Sunda subduction zone may generate tsunamigenic earthquakes with a magnitude range from M w 8.8 to M w 9.0.…”
Section: Earthquake Scenario Selectionmentioning
confidence: 99%
See 3 more Smart Citations